Individuality, subjectivation, and their civic significance in contemporary China: The cultivation of an ethical self in a cultural community. (November 2019) - Yi, Lin
Drawing upon ethnographic data collected from fieldwork among a reading-based community in a coastal city over 10 years, and Michel Foucault's notion of the cultivation of an ethical self, the primary aim of this study is to examine three issues: (1) how do middle-class citizens articulate and practise the cultural activities that they advocate?; (2) are their practices simultaneously individualized and totalized in the way that Foucault demonstrates?; and (3) do these internally oriented practices have civic significance?